Impaired Cellular Immunity to SARS-CoV-2 in Severe COVID-19 Patients - Ni, Ling; Cheng, Meng-Li; Feng, Yu; Zhao, Hui; Liu, Jingyuan; Ye, Fang; Ye, Qing; Zhu, Gengzhen; Li, Xiaoli; Wang, Pengzhi; Shao, Jing; Deng, Yong-Qiang; et al. (Frontiers in Immunology, 2021)
The high infection rate and rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) make it a world-wide pandemic. Individuals infected by the virus exhibited different degrees of symptoms, and most convalescent individuals have been shown to develop both cellular and humoral immune responses. However, virus-specific adaptive immune responses in severe patients during acute phase have not been thoroughly studied. Here, we found that in a group of COVID-19 patients with acute respiratory distress syndrome (ARDS) during hospitalization, most of them mounted SARS-CoV-2-specific antibody responses, including neutralizing antibodies. However, compared to healthy controls, the percentages and absolute numbers of both NK cells and CD8+ T cells were significantly reduced, with decreased IFN expression in CD4+ T cells in peripheral blood from severe patientsMost notably, their peripheral blood lymphocytes failed in producing IFN against viral proteins. Thus, severe COVID-19 patients at acute infection stage developed SARS-CoV-2-specific antibody responses but were impaired in cellular immunity, which emphasizes on the role of cellular immunity in COVID-19.